Differences between best Olympic results and best world athletics events' throws women accomplished in the Olympic games' years - Milinovic, I.; Milanovic, D.; Harasin, D. (Acta Kinesiologica, 2013)
The aim of the research was to determine differences between vectors of arithmetic means of the best results in athletics throwing events accomplished in the finals of Olympic Games and the results of 8 world seasons` best throwers achieved at other competitions in the same years. The sample of subjects consisted of women athletes, elite shot putters and discus, javelin and hammer throwers from different countries who competed in the Olympic Games` finals and those who were, in the same years, positioned among first eight on the world ranking lists. The collected data were processed by the software package Statistica 7.0. Module t-test for dependent samples was used to analyze statistical significance of the differences between arithmetic means of the best results achieved at the Olympic Games finals and the best results achieved at other competitions in the same years. The thesis was rejected that there were no statistical significant differences between the best results achieved at the Olympic Games and the results of the world best 8 women throwers accomplished at other competitions in the Olympic years for all throwing events.